Impact of the N5-proximal Asn on the Thermodynamic and Kinetic Stability of the Semiquinone Radical in Photolyase - Damiani, Michael J. (American Society for Biochemistry and Molecular Biology, 2011)
Flavoproteins can dramatically adjust the thermodynamics and kinetics of electron transfer at their flavin cofactor. A versatile regulatory tool is proton transfer. Here, we demonstrate the significance of proton-coupled electron transfer to redox tuning and semiquinone (sq) stability in photolyases (PLs) and cryptochromes (CRYs). These light-responsive proteins share homologous overall architectures and FAD-binding pockets, yet they have evolved divergent functions that include DNA repair, photomorphogenesis, regulation of circadian rhythm, and magnetoreception. We report the first measurement of both FAD redox potentials for cyclobutane pyrimidine dimer PL (CPD-PL, Anacystis nidulans). These values, E(1)(hq/sq) = −140 mV and E(2)(sq/ox) = −219 mV, where hq is FAD hydroquinone and ox is oxidized FAD, establish that the sq is not thermodynamically stabilized (ΔE = E(2) − E(1) = −79 mV). Results with N386D CPD-PL support our earlier hypothesis of a kinetic barrier to sq oxidation associated with proton transfer. Both E(1) and E(2) are upshifted by ∼100 mV in this mutant; replacing the N5-proximal Asn with Asp decreases the driving force for sq oxidation. However, this Asp alleviates the kinetic barrier, presumably by acting as a proton shuttle, because the sq in N386D CPD-PL oxidizes orders of magnitude more rapidly than wild type. These data clearly reveal, as suggested for plant CRYs, that an N5-proximal Asp can switch on proton transfer and modulate sq reactivity. However, the effect is context-dependent. More generally, we propose that PLs and CRYs tune the properties of their N5-proximal residue to adjust the extent of proton transfer, H-bonding patterns, and changes in protein conformation associated with electron transfer at the flavin.